Teachers' Trends toward Using the Electronic Management Program (Fares) in Public Education Schools in Al-Dawadmi Governorate - Alrashide, Sarah Mohmmed (Journal of Educational and Psychological Sciences, 2020)
This study aims to define the trends toward using the electronic management program (Fares) in developing the management aspects, and self-service field. It was Used the descriptive surveyor approach, the questionnaire as a tool for data collection, and the study population consists of all the teachers in Al-Dawadmi Governorate (3714). The sample of the study will be chosen by 5% who are (186) teachers. The research seeks to the following results, It was found that the degree of trends of teachers towards the use of electronic management program "Fares" in the management work was positive and has a high value, It was found that the degree of trends of teachers towards the use of the electronic management program "Fares" in the field of self-service was positive and has a high value, The results of the research showed the existence of obstacles faced by the teachers while using the program from their point of view.
Keywords: educational administration; electronic management; teacher attitudes; fares program; administrative development